THE PECULIARITY OF SPIRITUALITY IN "PUANCARE" - Rushana Zaripova (Galaxy International Interdisciplinary Research Journal, 2023)
It is impossible for a child not to be like the parents who gave birth to him. When analyzing and interpreting a work of art, naturally, we witness that the writer's mental state and mood are transferred to it. That is, in the works of any artist, first of all, he reflects his soul, his spiritual world. In fact, the well-known writer Abduqayum Yoldosh also conveys his subconscious ideas, emotional experiences and psychological worldview to readers with high artistry through his large and small works. As a result, the reader who gets acquainted with the author's works becomes more attached to the creative world of the author. This article talks about the image of the psyche and its peculiarities in the story "Poincaré" written by the writer.